Memory CD8+ T Cell Protection From Viral Reinfection Depends on Interleukin-33 Alarmin Signals - Baumann, Claudia; Fröhlich, Anja; Brunner, Tobias M.; Holecska, Vivien; Pinschewer, Daniel D.; Löhning, Max (Frontiers in Immunology, 2019)
Memory CD8+ cytotoxic T lymphocytes (CTLs) can protect against viral reinfection. However, the signals driving rapid memory CTL reactivation have remained ill-defined. Viral infections can trigger the release of the alarmin interleukin-33 (IL-33) from non-hematopoietic cells. IL-33 signals through its unique receptor ST2 to promote primary effector expansion and activation of CTLs. Here, we show that the transcription factor STAT4 regulated the expression of ST2 on CTLs in vitro and in vivo in primary infections with lymphocytic choriomeningitis virus (LCMV). In the primary antiviral response, IL-33 enhanced effector differentiation and antiviral cytokine production in a CTL-intrinsic manner. Further, using sequential adoptive transfers of LCMV-specific CD8+ T cells, we deciphered the IL-33 dependence of circulating memory CTLs at various stages of their development. IL-33 was found dispensable for the formation and maintenance of memory CTLs, and its absence during priming did not affect their recall response. However, in line with the CTL-boosting role of IL-33 in primary LCMV infections, circulating memory CTLs required IL-33 for efficient secondary expansion, enhanced effector functions, and virus control upon challenge infection. Thus, beyond their effector-promoting activity in primary immune reactions, innate alarmin signals also drive memory T cell recall responses, which has implications for immunity to recurrent diseases.